The Land of Stories - An author's odyssey - Colfer, Chris 1990- (Little, Brown and Company, 2016)
"Conner learns that the only place to fight the Masked Man's literary army is inside his own short stories. When the twins and their friends enter worlds crafted from Conner's imagination, the race begins to put an end to the Masked Man's reign of terror"...
Keywords: Characters in literature; Imagination; Twins; Brothers and sisters; Magic; Youths' writings; Kinderbuch